1997
DOI: 10.1038/sj.leu.2400521
|View full text |Cite
|
Sign up to set email alerts
|

Mutation analysis of the WT1 gene in sporadic childhood leukaemia

Abstract: Peripheral blood and bone marrow samples from patients less

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 1 publication
0
18
0
Order By: Relevance
“…The present report is the ®rst to demonstrate that constitutive expression of WT1 in leukemic cell lines can lead to impairment of some di erentiation responses, suggesting that downregulation of WT1 indeed may be a prerequisite for terminal differentiation. WT1 antisense oligomers inhibit the cell growth of both leukemic cell lines and fresh leukemic cells from patients with acute or chronic myeloid leukemia, but not normal colony-forming-unit granulocyte-macrophage (CFU-GM) (Algar et al, 1996;Yamagami et al, 1996). This indicates that the WT1 protein may be important for the sustained proliferation of leukemic cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present report is the ®rst to demonstrate that constitutive expression of WT1 in leukemic cell lines can lead to impairment of some di erentiation responses, suggesting that downregulation of WT1 indeed may be a prerequisite for terminal differentiation. WT1 antisense oligomers inhibit the cell growth of both leukemic cell lines and fresh leukemic cells from patients with acute or chronic myeloid leukemia, but not normal colony-forming-unit granulocyte-macrophage (CFU-GM) (Algar et al, 1996;Yamagami et al, 1996). This indicates that the WT1 protein may be important for the sustained proliferation of leukemic cells.…”
Section: Discussionmentioning
confidence: 99%
“…U937 clones expressing WT1 show similar growth rate and viability in suspension culture as control cells WT1 has been reported to in¯uence proliferation and viability of some cells Luo et al, 1995;Werner et al, 1995;Algar et al, 1996;Yamagami et al, 1996). Therefore, we determined the growth rate in suspension culture of the WT1(7KTS) and WT1(+KTS) transfected cells.…”
Section: Establishment and Characterization Of U937 Clones Constitutimentioning
confidence: 91%
“…For these experiments, we chose two breast cancer cell lines that express different levels of endogenous WT1, a human leukemia cell line K562 that expresses high levels of WT1 and has previously been shown to undergo apoptosis when WT1 expression is blocked (Algar et al, 1996), and Cos-7 cells that have no WT1 expression. In our studies, we found that the c-myc promoter, especially a region between À107 and þ 36, is capable of responding to WT1 with increased expression in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Exons 7-10 were amplified from gDNA using primers and conditions described in Algar et al 16 PCR products were gelpurified and subjected to direct sequencing using the ABI PRISM dideoxy terminator automated sequencing protocols of Applied Biosystems. Alternative splicing at the ϩ/Ϫ KTS site within exon 9 was examined using methods described previously.…”
Section: Mutation Analysismentioning
confidence: 99%